Tunnel liner subjected to excavation loading - George, K. P. (Penerbit UTM Press, 1981)
A laboratory study is conducted to estimate moments, thrusts and deformation in a tunnel liner subjected to ‘excavation loading\ The effects of thrust, moment and deformation of the depth of burial are examined and the results are compared with the solutions offered by Burns and Richard (1964) and by Morgan (1961) and the finite element solutions of Mohraz et al. (1975). The researcher concludes that the agreement between the experimentally determined load values and those calculated from Morgan (1961) is so good that the latter are applicable to the design of tunnel liners to be deeply buried and subjected to excavation loading. In problems of shallow cover, however, reliable estimates of thrust, moment and deflection can be obtained by using rigid liner equations.